2015
DOI: 10.1016/j.coldregions.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A decision support model to assess the braking performance on snow and ice contaminated runways

Abstract: Pilots need accurate predictions on the quality of runway surface conditions when operating on snow/ice contaminated runways. These predictions are typically made by friction measurements, or by expert judgments of runway inspectors. This study presents a decision support model (the IRIS runway model) for runway inspectors that interprets descriptive data from SNOWTAM reports and predicts the braking action on the common scale from 1 to 5, ranging from "poor" to "good". The model is tested on two airports in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Pilots need accurate predictions on the quality of runway surface conditions when operating on runways disrupted by snow/ice. These predictions are typically made by friction measurements, or by expert judgments of runway inspectors [16]. Maintaining operational safety and the status of airport runways during snowfall events is a challenging issue with which many airports are grappling.…”
Section: Winter Maintenance Of Airportmentioning
confidence: 99%
“…Pilots need accurate predictions on the quality of runway surface conditions when operating on runways disrupted by snow/ice. These predictions are typically made by friction measurements, or by expert judgments of runway inspectors [16]. Maintaining operational safety and the status of airport runways during snowfall events is a challenging issue with which many airports are grappling.…”
Section: Winter Maintenance Of Airportmentioning
confidence: 99%
“…In order to predict the surface conditions before aircrafts hit the ground, there have been conducted studies on how available surface friction is affected by weather conditions and runway contamination based on engineeringand physics-based models and basic statistical approaches. Klein-Paste et al [32] proposed a runway model for the surface conditions which interprets descriptive data from the international standardized runway reports called Snowtam reports. The model evaluates a sum of seven effects that contain information about the runway contamination as well as measurement of runway temperature and humidity, P = 7 i=1 x i .…”
Section: Introductionmentioning
confidence: 99%
“…The scenario model was further developed in Huseby & Rabbe [21], where it was shown that the scenario model could be improved by optimizing the thresholds for the scenarios according to Type 1 and Type 2 errors using weather and flight data. Both Huseby & Rabbes [20] scenario model and the runway model of Klain-Paste et al [32] are used in an integrated runway information system called IRIS, which is implemented on 16 Norwegian airports to support in safer operations of Norwegian airports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, more than 100 airports meet with heavy snow or frozen ice in winter, which causes brake failing or accidents easily [ 1 – 3 ]. For avoiding accidents, most airports close runways and use the deicing chemicals [ 4 ] or machines [ 5 – 7 ] to remove snow.…”
Section: Introductionmentioning
confidence: 99%